Extent and Evaluation of Flash Flood Resilience in Mountainous Communities of Daral and Chail Valleys, District Swat, Pakistan: Flash Flood Resilience in Mountainous Communities - Khan, Muhammad Barkat Ali; Atta-ur-Rahman (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
This study aimed to explore the extent and evaluation of flash flood resilience in mountainous communities of Daral and Chail valleys of Swat. After collecting data from primary and secondary sources, the parameters of Disaster Resilience Capacity (DRC) model was applied for data analysis. The analysis reveals that stream discharge increases during summer mainly because of the rapid melting of snow, ice, glaciers and monsoonal rains, which results in flash floods. The communities living in the mountainous areas of Daral and Chail valleys face problems of multitudes of socio-economic and infrastructural flash flood damages almost every year. However, limited communities have adopted indigenous resilience strategies to bounce back from the recurrent adverse impacts of flash floods. It was found from the analysis that due to indigenous resilience practices by the local communities and the location of most mountainous communities, Daral valley is more resilient to flash floods as compared to Chail valley. Contrary to this, the extent and level of flash flood resilience in Chail valley are low as most of the mountainous communities are more vulnerable to seasonal flash floods. Some wise practices can enhance resilience to flash floods, especially land use planning, community preparedness, afforestation, and improved accessibility and communications.